(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The essay analizes the role Sicilian women played, in the fourteenth and fifteenth centuries, as guardians, proxies, and witnesses, and their space in the context of judicial activities, by comparing the legal norms of the customary laws of Sicilian cities and terre with the information provided by the documents kept in the Archivio di Stato di Palermo, first of all, in the registers of the fund Notai. They show the importance of reach widows as administrators of the family estate and of women, in general, as proxies of their children and husbands. Unlike wealthy women, generally, the less well-off were not obliged to remain widows in order to be guardians of their minor children. We can find female witnesses in convents, trials against magicians and matrimonial trials. We observe that women’s testimonies were rejected for moral or sexual reasons, in addition to perjury.